The Effect of Collage Playing Therapy on Increasing the Concentration of Autistic Children with ADHD at the Permata Ananda Autism Therapy Center, Yogyakarta - Ratih Dwilestari Puji Utami; Maharani Annisa Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
ABSTRACT Background: Autism is defined as a disorder of neurobiological development which results in language, behavior, cognitive, and social interaction disorders. Attention Deficit Hyperactivity Disorder (ADHD) is also a neurobiological disorder that causes children to experience attention deficit disorder, self-control, and tend to always look for stimulation. The application of play therapy is carried out to provide a therapeutic effect for children and to have a significant effect on increasing concentration and attention. Purpose: This study aims to determine whether there is any effect of playing collage therapy on increasing the concentration of children with autism accompanied by Attention Deficit Hyperactivity Disorder (ADHD) at the Permata Ananda Autism Therapy Center, Yogyakarta. Methods: The research design was a pre-experimental design, using one group pre-test and post-test design. The number of samples in this study were 15 respondents, using the Total Sampling Technique. Data collection used a checklist that was filled out during the pre, intervention and post tests and used the Wilcoxon data analysis test. Results: The results of the analysis of the effect of playing collage therapy on increasing concentration based on the checklist, the p-value is 0.001 <0.05, so there is a significant difference so that there is an effect between playing collage therapy and increasing concentration in autistic children with ADHD. Conclusion: The results of this study can be used as a reference material in increasing the concentration of autistic children with ADHD through collage play therapy. Keywords : ADHD, Autism, Collage, Concentration